Distribution and biodiversity of benthic macroalgae in the Nanji Islands, China - Xin Wang; Shangwei Xie; Wandong Chen; Xiaopin Ni; Wantao Xu; Qijun Luo; Haimin Chen (Frontiers in Marine Science)
IntroductionThis study focuses on the benthic macroalgae of the Nanji Islands, China, aiming to assess species diversity and biomass through a combination of qualitative and quantitative approaches using historical data.MethodsWe conducted a comprehensive survey of the benthic macroalgae, employing species identification and biomass estimation techniques across different seasons and tidal zones. Co-occurrence network analysis was used to explore species interactions and ecosystem stability. Historical data were compared to recent monitoring results to evaluate the impacts of marine reserves.ResultsA total of 127 species were identified, with Rhodophyta being the dominant group (57.48%), exhibiting remarkable ecological adaptability. Seasonal variation in biomass showed peaks in spring (1344.31 g·m⁻²) and the lowest in autumn (428.78 g·m⁻²). The mid/low-tide zones supported 2.6 times higher biomass than the high-tide zones. The southern communities demonstrated increased stability, with a co-occurrence network of 129 nodes and 999 edges. Biomass recovery of 61.14% was observed at key monitoring sites since the establishment of protected areas in 1990.DiscussionOur findings emphasize the crucial role of marine reserves in reversing biodiversity loss and maintaining ecosystem health. The observed biomass recovery and species diversity restoration in protected areas underscore the effectiveness of these conservation strategies. The study also provides valuable insights into the distribution patterns of benthic macroalgae, highlighting the significance of seasonal and tidal zone influences on biodiversity and biomass.